Effects of various water medications on performance and feed and water consumption by pigs weaned at 3 or 4 weeks of age - G L Allee; D Schoneweis (Kansas Agricultural Experiment Station Research Reports, 1979)
Two trials using 216 pigs were conducted to evaluate effects various water medications have on performance and feed and water consumption by pigs weaned at 3 and 4 weeks of age. Water medication had no effect on pig performance. Pigs weaned at 3 weeks of age consumed an average of 0.8 quart of water per day for the first five days after weaning, compared with an average of 1.1 quarts per day by those weaned at 4 weeks of age. Adding syrup (500 ml/5 gallon) doubled the water consumption of both groups. Water medications did not reduce water consumption.; Swine Day, Manhattan, KS, November 8, 1979
Keywords: Swine day; 1979; Kansas Agricultural Experiment Station contribution; no. 80-136-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 371; Swine; Water medications; Performance; Water consumption